2014
DOI: 10.1371/journal.pone.0110441
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 2 Mediates Ischemia-Reperfusion Injury of the Small Intestine in Adult Mice

Abstract: Toll-like receptor 2 (TLR2) recognizes conserved molecular patterns associated with both gram-negative and gram-positive bacteria, and detects some endogenous ligands. Previous studies demonstrated that in ischemia-reperfusion (I/R) injury of the small intestine, the TLR2-dependent signaling exerted preventive effects on the damage in young mice, but did not have a significant effect in neonatal mice. We investigated the role of TLR2 in adult ischemia-reperfusion injury in the small intestine. Wild-type and TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
(48 reference statements)
2
10
1
Order By: Relevance
“…Using a 45 min ischemic period followed by 60 min reperfusion, a recent study also demonstrated that the neutrophilic infitration, Cox-2 and TNF mediated at least a portion of IR-induced intestinal damage in a TLR2 dependent manner (26). These studies differ from those performed on young (4 wk) mice in which wildtype mice sustained minimal intestinal injury (0.67 injury score on a 0–4 scale) and TLR2 −/− mice exhibited increased injury (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a 45 min ischemic period followed by 60 min reperfusion, a recent study also demonstrated that the neutrophilic infitration, Cox-2 and TNF mediated at least a portion of IR-induced intestinal damage in a TLR2 dependent manner (26). These studies differ from those performed on young (4 wk) mice in which wildtype mice sustained minimal intestinal injury (0.67 injury score on a 0–4 scale) and TLR2 −/− mice exhibited increased injury (39).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, TLR2 plays a role in renal, cerebral, and myocardial IR (18, 24, 25). A recent publication indicated that TLR2 is required for the cellular response to intestinal IR (26). However, the role of TLR2 in antibody deposition and complement activation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However some studies on neutrophils' role in the local small intestine damage following intestinal IR report contradictory findings (Kurtel et al 1991;Simpson et al 1993;Matthijsen et al 2009), and its role in intestinal IR is still unclear. In a recent study, depletion of circulating neutrophil attenuated the IR injury in the small intestine in wild-type mice (Watanabe et al 2014). In our study, and although not statistically significant, the number of neutrophils present within the lamina propria at the level of the top of the villi, in the duodenum, was higher in groups 1 and 2 than in the control group (group 3).…”
Section: Histopathology Discussioncontrasting
confidence: 62%
“…Although typical time for evaluation of tissue damage after reperfusion is 2-3 hr, longer time (12 hr) is required for the analysis of intestinal stem cell mobilization 36 . Additionally, changes in commensal microbiota and TLR/Nod-mediated signaling can significantly influence the outcome of the of IR injury 4,8,[37][38][39] .…”
Section: Discussionmentioning
confidence: 99%